Prevalence of vitamin D deficiency in patients of hypertensive disorders of pregnancy and normal pregnant women - Sharma, Asha; Choudhary, Jaya; Joshi, Piyush; Bardhar, Neha (International Journal of Research in Medical Sciences, 2020)
Background: The aim of this study was to compare vitamin D level in normal pregnant women and patients of hypertensive disorders of pregnancy and to study the prevalence of vitamin D deficiency in patients of hypertensive disorders of pregnancy and normal pregnant women. Methods: 50 women affected by hypertensive disorders of pregnancy and 50 normal pregnant women more than 20 weeks of gestation, admitted to the ward or to labour room in the Obstetrics and Gynaecology Department, of Mahatma Gandhi Medical College and Hospital were enrolled in the study. Assessment of serum 25 hydroxy vitamin D was done by chemiluminescent immunoassay method. Results: Serum vitamin D levels were low in women with hypertensive disorders of pregnancy with mean serum vitamin D level 13.66±7.358 ng/ml as compared to normal normotensive pregnant women 21.14±8.241ng/ml, which is statistically significant (p=0.001). Mean vitamin D level in study population was 17.40±8.634 ng/ml. The prevalence of vitamin D deficiency in hypertensive disorders of pregnancy group was very high 88% compared to 50% in normal normotensive pregnant women group. The difference was statistically significant (p=0.001). vitamin D deficiency was found among 69% in study population. Conclusions: Vitamin D levels are deficient in patients of hypertensive disorders of pregnancy as compared to normal pregnant women. There is increased prevalence of vitamin D deficiency with hypertensive disorders of pregnancy suggesting that vitamin D deficiency can be a risk factor for the development of hypertensive disorders of pregnancy.